PENGARUH INOVASI DAN KUALITAS PRODUK TERHADAP KINERJA BISNIS USAHA KECIL MENENGAH MAKANAN SIAP SAJI D’BESTO - Indra Permana (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2018)
This study aims to explain the influence of innovation and product quality to the business performance of UKM Mini Resto D'Besto in address Setia Mekar, Setia Mekar subdistrict, Tambun – Bekasi. Either partiially or simultaneously (together). In this study, the population and the sample is a consumer of these UKM totaling 60 responden.Dengan using quantitative research and sampling techniques were used, namely, probability sampling and simple random sampling. Thus the second hypothesis on research which states that the Innovation and Quality Products variables are variables which equally affect the business performance is proven and can be accepted. This suggests that consumers would be interested in buying Chicken D'Besto if innovation and good quality of products offered. Keywords:Innovation, Product Quality, Business Performance